Ciliary Neurotrophic Factor Protects Striatal Neurons against Excitotoxicity by Enhancing Glial Glutamate Uptake - Beurrier, Corinne; Faideau, Mathilde; Bennouar, Khaled-Ezaheir; Escartin, Carole; Kerkerian-Le Goff, Lydia; Bonvento, Gilles; Gubellini, Paolo (PloS one, 2010)
Ciliary neurotrophic factor (CNTF) is a potent neuroprotective cytokine in different animal models of glutamate-induced excitotoxicity, although its action mechanisms are still poorly characterized. We tested the hypothesis that an increased function of glial glutamate transporters (GTs) could underlie CNTF-mediated neuroprotection. We show that neuronal loss induced by in vivo striatal injection of the excitotoxin quinolinic acid (QA) was significantly reduced (by approximately 75%) in CNTF-treated animals. In striatal slices, acute QA application dramatically inhibited corticostriatal field potentials (FPs), whose recovery was significantly higher in CNTF rats compared to controls (approximately 40% vs. approximately 7%), confirming an enhanced resistance to excitotoxicity. The GT inhibitor DL-threo-beta-benzyloxyaspartate greatly reduced FP recovery in CNTF rats, supporting the role of GT in CNTF-mediated neuroprotection. Whole-cell patch-clamp recordings from striatal medium spiny neurons showed no alteration of basic properties of striatal glutamatergic transmission in CNTF animals, but the increased effect of a low-affinity competitive glutamate receptor antagonist (gamma-D-glutamylglycine) also suggested an enhanced GT function. These data strongly support our hypothesis that CNTF is neuroprotective via an increased function of glial GTs, and further confirms the therapeutic potential of CNTF for the clinical treatment of progressive neurodegenerative diseases involving glutamate overflow.